Assessment for learning in a Malaysian ESL primary school context / Sedigheh Abbasnasab Sardareh - Sedigheh, Abbasnasab Sardareh (2014)

(untitled)
This study was prompted by an uncertainty about the effectiveness claims for assessment for learning (AfL) strategies teachers implement in their classrooms. Literature indicates that teachers do not have enough knowledge and skills to implement AfL to the spirit. They have difficulty developing learner autonomy while implementing AfL. Adopting a sociocultural theoretical perspective that considers learning as taking part in a community of practice and regards AfL strategies and teacher-students and student-student interactions as patterns of participation that can bridge the learning gap and help students become the owners of their own learning, this study concerned AfL in Year One and Year Two primary school ESL classes in Malaysia and aimed to investigate how teachers implement classroom discussion and questioning during AfL and how they provide students with formative feedback. This qualitative case study was conducted in a selected primary school around Selangor. The school was selected based on specific criteria using purposive sampling. Year One and Year Two ESL teachers at the selected school and their students took part in this study. Interviews, classroom observations and relevant documents were used to collect data. Themes were identified through the process of constant comparison using Nvivo 10 software and the emergent themes were interpreted within a sociocultural theoretical framework. The data revealed that the teachers asked many questions to build a learning community and guide the students into the preferred practices. However, most of the questions asked by the teachers were lower cognitive questions that did not provoke thoughtful reflection and the importance of strategic questioning to foster autonomy as a social construct was overlooked. Those who knew the answers responded immediately and other students did not have the opportunity to answer the questions, share the processes of learning ownership, collaborate with their peers and progress within the social safety of the peer culture. A supportive and collaborative learning environment was not provided for the iv students and hierarchical unequal patterns of participation were observed during the discussions. During whole class discussions, the students rarely asked questions and most of the time the teachers themselves were the only ones who talked and posed questions. The data showed that the discussions were dominated by certain students and highly controlled by the teachers. When some students dominated the discussions, others preferred to become more peripheral and some of them developed an identity of non-participant and increasingly became marginalized. Teacher feedback to the students was mostly in the form of praise and one-to-one instruction. It was observed that feedback was not dialogic to help the students actively participate in the feedback process, negotiate meaning and develop a shared ownership of learning. Highlighting the importance of teacher-students and student-student relationships in successful implementation of AfL helps policy makers and stakeholders to develop new ways of enhancing teachers’ capacity to build new patterns of participation in the classroom and implement AfL strategies with the aim of developing more autonomous learners.